2(3z-1)-2(5-2z)=4

Simple and best practice solution for 2(3z-1)-2(5-2z)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3z-1)-2(5-2z)=4 equation:


Simplifying
2(3z + -1) + -2(5 + -2z) = 4

Reorder the terms:
2(-1 + 3z) + -2(5 + -2z) = 4
(-1 * 2 + 3z * 2) + -2(5 + -2z) = 4
(-2 + 6z) + -2(5 + -2z) = 4
-2 + 6z + (5 * -2 + -2z * -2) = 4
-2 + 6z + (-10 + 4z) = 4

Reorder the terms:
-2 + -10 + 6z + 4z = 4

Combine like terms: -2 + -10 = -12
-12 + 6z + 4z = 4

Combine like terms: 6z + 4z = 10z
-12 + 10z = 4

Solving
-12 + 10z = 4

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 10z = 4 + 12

Combine like terms: -12 + 12 = 0
0 + 10z = 4 + 12
10z = 4 + 12

Combine like terms: 4 + 12 = 16
10z = 16

Divide each side by '10'.
z = 1.6

Simplifying
z = 1.6

See similar equations:

| 3p-1=5(p-1)-2(7-7-2p) | | 5y^4-7y^3-6y^2=0 | | -5(3-2y)+4y=3 | | 3(4z-3)-3(2-3z)=12 | | 125v^2-320=0 | | 5-6r-3=-4 | | 2a+1=12 | | 8y-10=4y+6 | | 16p^2-1=0 | | n+1.08=15.72 | | x-13=5x+3 | | f(x)=4x^3+9 | | X+8+3x=-24 | | e+3.65=-1.4 | | -2a-(9)=23 | | (4-11i)(-6+5i)= | | 2(t-3)=4(t+2) | | 24=7x-6-2x | | .2=62 | | 15k+5=5(2x-3) | | -8(4+v)=64 | | 3x-9=3(-3+1x) | | 2x+4+x=4x+4-x | | 8x^2+22x-76=0 | | 62=.2 | | 5d-8=5(1d+3) | | p(t)=-2t^2+5t+8 | | 2a+b=-16 | | 5(-7x+3)=-265 | | 6n+3(8n+5)=255 | | 2xy-6y= | | 9y-2(y+14)=84 |

Equations solver categories